PELATIHAN MANAJEMEN SANGGAR SENI DI SMAN 1 SUWAWA BONE BOLANGO - Riana Diah Sitharesmi (Journal of Community Services on Multidisciplinary Sciences, 2026)
An Art centre in school is currently an informal unit that is much needed, especially to strengthen artistic skills for high school students. The establishment of an art centre at SMAN 1 Suwawa, Bone Bolango Regency, will also be able to accommodate the school's preparation for participating in the annual FLS3N agenda. To help the school in preparing the establishment of an art centre, we provided brief training and mentoring on art management for students at SMAN 1 Suwawa. The training was carried out through a participatory workshop method on management to prepare the art's organisational structure, and staging drama, dance, and music to provide the initial repertoire of the centre. The training was integrated with performing arts activities in commemorating the anniversary of SMAN 1 Suwawa. The results obtained from this program are the basic knowledge and skills of the participants of how to manage an art centre at school, and a complete repertoire of creative dance, choir, and monologue as a respective initial capita